A review of RSPCA research into wildlife rehabilitation. (23rd February 2013) - Grogan, A.; Kelly, A.
Abstract : Wildlife rehabilitation is defined as 'the treatment and temporary care of injured, diseased, and displaced indigenous animals, and the subsequent release of healthy animals to appropriate habitats in the wild' (Miller 2012). Vets are frequently presented with wildlife casualties and although there are a number of texts available to help vets with the treatment of wild animals, such as the BSAVA Manual of Wildlife Casualties (Mullineaux and others 2003) and papers produced by experienced wildlife vets (eg, Bexton and Couper 2010, Couper and Bexton 2012), there still remains questions regarding which individual animals can, or should, be treated, which animals will survive treatment and which animals will survive after they have been released back to the wild. The RSPCA believes that the welfare of wildlife casualties can be improved by investigating which injuries or illnesses are most likely to result in a successful release for each species, and by collecting data on postrelease survivorship. As a result, there have been a number of papers published based on the work of the RSPCA's four wildlife centres: East Winch in Norfolk, Mallydams Wood in East Sussex, Stapeley Grange in Cheshire and West Hatch in Somerset. This paper summarises this research, to guide those in the profession with an interest in this subject to papers that may prove useful to them.